Back Cover: Highly Active Supported Pt Nanocatalysts Synthesized by Alcohol Reduction towards Hydrogenation of Cinnamaldehyde: Synergy of Metal Valence and Hydroxyl Groups (Chem. Asian J. 7/2015). Issue 7 (July 2015) - Wang, Yanyan; He, Wanhong; Wang, Liren; Yang, Junjiao; Xiang, Xu; Zhang, Bing; Li, Feng
<x xml:space="preserve">Abstract</x> Nanocatalysts. The Back Cover picture illustrates supported platinum nanocatalysts over layered hydrotalcite for the selective hydrogenation of cinnamaldehyde (CMA) to cinnamyl alcohol (CMO). The small‐sized Pt catalyst shows an unusually high selectivity towards the C=O bond and the highest activity among all catalysts. This is attributable to the synergy of the cationic Pt2+ species and the abundant hydroxyl groups on the hydrotalcite. The hydroxyl groups, as in situ alkali promoters, improve the selectivity towards C=O hydrogenation. In their Full Paper on page 1561, Xu Xiang, Bing Zhang et al. highlight the synergic contributions of active metal valence and native promoter on the catalytic hydrogenation.